Influence of Field Spacer Geometry on the Performance of a High Voltage Coaxial Type Transmission Line with Solid Dielectric Spacer in Vacuum - Anagha, A. P.; Sunitha, K. (Engineering, Technology & Applied Science Research, 2017)
With the development of more powerful high power electromagnetic sources, the transmission of high voltage power particularly between pulsed power systems to huge power rated microwave sources in absence of electrical breakdown and pulse distortion has begun to become a vital issue. A high voltage coaxial type transmission line with 500 kV peak voltage in vacuum is proposed. A novel proposal of configuration bearing a positive angle of 45o with socket-type filed shaper is being discussed in this paper in a manner to improve surface flashover properties and also to decrease the distortion seen in the pulse shape. This type of transmission line provides high capability of hold off voltage. The electric field distribution of the coaxial geometry with different field shaper configurations and different spacer parameters are also investigated using COMSOL software.